2023
DOI: 10.48550/arxiv.2301.10787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling physics beyond the standard model with classical and quantum anomaly detection

Abstract: Much hope for finding new physics phenomena at microscopic scale relies on the observations obtained from High Energy Physics experiments, like the ones performed at the Large Hadron Collider (LHC). However, current experiments do not indicate clear signs of new physics that could guide the development of additional Beyond Standard Model (BSM) theories. Identifying signatures of new physics out of the enormous amount of data produced at the LHC falls into the class of anomaly detection and constitutes one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Once such a quantum embedding is realized, a decision rule to carry out the desired classification task can be obtained directly from the fidelity between the encoded feature vectors [ 20 ] or by passing the resulting quantum kernel to a classical support vector machine [ 18 , 19 ]. Soon after the introduction of quantum kernel methods, it was shown that quantum kernel methods, equipped with the right quantum feature maps, can solve certain specifically designed problems more efficiently than any known classical counterpart [ 21 ], thus motivating a large body of research aimed at finding similar advantages in more generic and applied contexts [ 22 , 23 , 24 ], including for the following: data analysis for high-energy physics [ 25 , 26 , 27 ], quantum phase classification [ 28 ], fraud detection [ 29 ] and virtual screening for drug discovery [ 30 ]. While some promising examples were identified [ 27 , 30 ], only proof-of-principle results have been achieved so far, mostly based on empirical considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Once such a quantum embedding is realized, a decision rule to carry out the desired classification task can be obtained directly from the fidelity between the encoded feature vectors [ 20 ] or by passing the resulting quantum kernel to a classical support vector machine [ 18 , 19 ]. Soon after the introduction of quantum kernel methods, it was shown that quantum kernel methods, equipped with the right quantum feature maps, can solve certain specifically designed problems more efficiently than any known classical counterpart [ 21 ], thus motivating a large body of research aimed at finding similar advantages in more generic and applied contexts [ 22 , 23 , 24 ], including for the following: data analysis for high-energy physics [ 25 , 26 , 27 ], quantum phase classification [ 28 ], fraud detection [ 29 ] and virtual screening for drug discovery [ 30 ]. While some promising examples were identified [ 27 , 30 ], only proof-of-principle results have been achieved so far, mostly based on empirical considerations.…”
Section: Introductionmentioning
confidence: 99%